Efficiency of the DNA repair and polymorphisms of the XRCC1, XRCC3 and XRCC4 DNA repair genes in systemic lupus erythematosus - Bassi, Carmen Lucia (2008)
Impaired DNA repair efficiency in systemic lupus erythematosus (SLE) patients has been reported in some studies, mainly regarding the repair of oxidative damage, but little is known about repair kinetics towards primarily single-stranded DNA breaks. In the present study, we aimed to investigate: (a) the efficiency of SLE peripheral blood leucocytes in repairing DNA damage induced by ionizing radiation and (b) the association of DNA repair gene (XRCC1 Arg399Gln, XRCC3 Thr241Met and XRCC4 Ile401Thr) polymorphisms in SLE patients, considering the whole group, or stratified sub-groups according to clinical and laboratory features. A total of 163 SLE patients and 125 healthy controls were studied. The kinetics of DNA strand break repair was evaluated by the comet assay, and genotyping for DNA repair genes was performed by PCR-RFLP. Compared with controls, SLE leucocytes exhibited decreased efficiency of DNA repair evaluated at 30 min following irradiation. A significant association with DNA repair gene polymorphisms was not observed for the whole group of SLE patients; however, the XRCC1 Arg399Gln polymorphism was associated with the presence of anti-dsDNA antibody. The concomitance of two DNA repair polymorphic sites was associated with the presence of neuropsychiatric manifestations and antiphospholipid antibody syndrome. Taken together, these results indicated that SLE leucocytes repair less efficiently the radiation-induced DNA damage, and DNA repair polymorphic sites may predispose to the development of particular clinical and laboratory features. © 2008 SAGE Publications.